Penyusunan Modul Projek Penguatan Profil Pelajar Pancasila: Strategi Optimalisasi Implementasi Kurikulum Merdeka Bagi Guru - Nina Farliana; Rusdarti; Wijang Sakitri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
The main issues involved in implementing an merdeka research program are Teachers' lack of understanding of the new learning model through the implementation of merdeka curriculum, leading to teachers' skills and understanding of module design being weak and teachers not having enough capacity. Use information technology to design learning models. learning processes and modules. interactive, aiming to create a generation of lifelong learners with the personality of Pancasila students. The goal of this service is to prepare teaching modules for the Pancasila student profile consolidation project aimed at implementing an merdeka research program at the secondary level, as well as analyzing the results of initial training. in preparing teaching modules for teachers. The location of the service is MGMP High School of Economics, Central Java Province. The target of the service is 54 high school economics teachers from Central Java province. The service deployment method starts with: The identification of practical problems, the empowerment process is carried out by increasing the understanding and knowledge of the concept of the Pancasila Student Profile Enhancement Project, workshops, discussions, questions, and answers as well as preparing simulations of project modules, as well as monitoring and evaluating the program. Service activities include initial coordination, implementation of workshops and skills building as well as regular supervision and consultation. Participants acquire specific skills in understanding and developing merdeka curriculum modules. The success of this service is demonstrated by the teachers' ability to prepare project plans to be implemented in their respective schools.